Achieving data saturation: evidence from a qualitative study of job satisfaction / Mohd Aliff Abdul Majid ... [et al.] - Abdul Majid, Mohd Aliff; Othman, Mohhidin; Mohamad, Siti Fatimah; Abdul Halim Lim, Sarina (Penerbit UiTM (UiTM Press), 2018)
The concept of saturation is deemed necessary in qualitative research; however, existing literature discussing the point of saturation is relatively scant. Previous qualitative studies tend to describe the point of saturation but fail to demonstrate how the saturation occurred. This article provides evidence on how qualitative research might report the point of data saturation. The original study consists of a mixed method approach to develop and validate an instrument for measuring offshore catering employees' job satisfaction. Notably, this paper reports a part of the qualitative portion of a mixed-method study. Using the data from a study involving 13 in-depth, semi-structured interviews, this study documents the degree of data saturation over the course of thematic analysis and demonstrates how data saturation was operationalised. Although the study reported 13 interviews, the saturation occurred within 12 interviews. The study findings are not extensively discussed; however, adequate information about the study background, data collection and sample characteristics are included. The technique presented in this paper provides practical guidance for qualitative researchers in reporting point of saturation. However, it is recommended that the evidence of data saturation occurred after 12 interviews should be applied with caution due to several factors.